Modified release itraconazole amorphous solid dispersion to treat Aspergillus fumigatus: importance of the animal model selection. (1st February 2017) - Maincent, Julien P.; Najvar, Laura K.; Kirkpatrick, William R.; Huang, Siyuan; Patterson, Thomas F.; Wiederhold, Nathan P.; Peters, Jay I.; Williams, Robert O.
Abstract: Previously, modified release itraconazole in the form of a melt-extruded amorphous solid dispersion based on a pH dependent enteric polymer combined with hydrophilic additives (HME-ITZ), exhibited improved in vitro dissolution properties. These properties agreed with pharmacokinetic results in rats showing high and sustained itraconazole (ITZ) systemic levels. The objective of the present study was to better understand the best choice of rodent model for evaluating the pharmacokinetic and efficacy of this orally administered modified release ITZ dosage form against invasive Aspergillus fumigatus . A mouse model and a guinea pig model were investigated and compared to results previously published. In the mouse model, despite similar levels as previously reported values, plasma and lung levels were variable and fungal burden was not statistically different for placebo controls, HME-ITZ and Sporanox ® (ITZ oral solution). This study demonstrated that the mouse model is a poor choice for studying modified release ITZ dosage forms based on pH dependent enteric polymers due to low fluid volume available for dissolution and low intestinal pH. To the contrary, guinea pig was a suitable model to evaluate modified release ITZ dosage forms. Indeed, a significant decrease in lung fungal burden as a result of high and sustained ITZ tissue levels was measured. Sufficiently high intestinal pH and fluids available for dissolution likely facilitated the dissolution process. Despite high ITZ tissue level, the primary therapeutic agent voriconazole exhibited an even more pronounced decrease in fungal burden due to its reported higher clinical efficacy specifically against Aspergillus fumigatus .